2002
DOI: 10.1080/10629360290002749
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of fast repair of DNA damage by cistanoside C and analogs: Mechanism and docking

Abstract: Experiments show that the natural substances phenylpropanoid glycosides (PPGs) extracted from pelicularis spicata are capable of repairing DNA damaged by oxygen radicals. Based on kinetic measurements and experiments on tumor cells, a theoretical study of the interaction between PPG molecules and isolated DNA bases, as well as a DNA fragment has been performed. An interaction mechanism reported early has been refined. The docking calculations performed using junction minimization of nucleic acids (JUMNA) softw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 45 publications
(33 reference statements)
0
8
0
Order By: Relevance
“…Hence, the phenolics considered as idyllic for maintaining the cellular redox level during photooxidative stress. Studies also showed that phenolics quickly repair DNA damage during the attack of free radical anions through electron transfer reaction (36). Flavonoids such as anthocyanin are the class of phenolics that enabled photo-oxidative stress tolerance in plants (37).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the phenolics considered as idyllic for maintaining the cellular redox level during photooxidative stress. Studies also showed that phenolics quickly repair DNA damage during the attack of free radical anions through electron transfer reaction (36). Flavonoids such as anthocyanin are the class of phenolics that enabled photo-oxidative stress tolerance in plants (37).…”
Section: Discussionmentioning
confidence: 99%
“…The rapid electron transfer reaction between the thymidine anion and caffeic acid has been reported by Zou et al (1995). Our previous studies (Li et al, 1997;Shi et al, 1999aShi et al, ,b, 2000Zhao et al, 2001Zhao et al, , 2003Gao et al, 2003;Sperandio et al, 2002) in chemical system also showed that many natural polyphenols can undergo electron transfer to ROSdamaged sites on DNA, finally repairing them and thereby eliminating the amount of both base damage and strand breaks. This mechanism for the reduction of DNA dysfunction arising from ROS attack could be significant at all different constituent levels of damaged DNA (Shi et al, 2008), from deoxynucleoside, deoxynucleotide, polydeoxynucleotide, single-stranded DNA, double-stranded DNA, to the integral DNA, which is more similar to cellular status.…”
Section: Introductionmentioning
confidence: 88%
“…We carried out two series of docking studies using one of the PPGs, Cistanoside C with two DNA fragments respectively, decamer ATGACGTCAT [23] and telomere (TTAGGG) n [24]. The following conclusions have been drawn from our studies: 1.…”
Section: Indroductionmentioning
confidence: 97%
“…In our preceding works [23,24], we have studied a proposed mechanism of interaction between PPG molecules and DNA fragments from both experimental and theoretical view points. We carried out two series of docking studies using one of the PPGs, Cistanoside C with two DNA fragments respectively, decamer ATGACGTCAT [23] and telomere (TTAGGG) n [24].…”
Section: Indroductionmentioning
confidence: 99%
See 1 more Smart Citation